Transferred depository for twenty-seven holotypes of the plant bug and flower bug species recently described from Thailand (Hemiptera: Heteroptera: Miridae and Anthocoridae) - Yasunaga, Tomohide; Yamada, Kazutaka; Morakote, Rut; Taekul, Charuwat; Duangthisan, Jomsurang (Zootaxa, 2016)
Between 2010 and 2013, twenty-six plant bug (Miridae) and one flower bug (Anthocoridae) species were described from Thailand by Yasunaga, Yamada and their colleagues. The original description of each species stated that the holotype depository was ‘SUT’ (Suranaree University of Technology, Nakhon Ratchasima, Thailand). Because continuous maintenance for type specimens in SUT would become difficult, with the consent of SUT, we have transferred the depository for each of the following holotype specimens from SUT to ‘DOAT’ (Insect Collection, Entomology & Zoology Group, Plant Protection Research and Development Office, Department of Agriculture, Bangkok). Accordingly, we herein provide the necessary information on each holotype specimen to properly satisfy ‘Recommendations 16C and 72F’ of the International Commission of Zoological Nomenclature (ICZN, 1999).